Barriers and Facilitators for Therapeutic Green Exercise in Patients with Chronic Conditions: A Qualitative Focus Group Study - Aristi Tsokani; Theodoros Dimopoulos; Evangelos Vourazanis; Nikolaos Strimpakos; Evdokia Billis; Garyfallia Pepera; Eleni Kapreli (Applied Sciences, 2023)
Background: Exercise has indisputable advantages for people with chronic conditions. Engaging in physical activity within natural environments, known as green exercise, contributes to both physical and mental well-being. The aim of this study was to investigate the perceptions of people with chronic conditions and health professionals and the perceived facilitators and barriers to therapeutic green exercise. Methods: This was a qualitative study based on two focus groups. Ethical approval was received, and a thematic analysis was used to analyze the discussions. Results: Seven patients and eight health professionals participated in the study. The thematic analysis yielded thirteen main themes. Safety concerns and inadequate infrastructures were key barriers. Core facilitators were socialization, and multisensory exposure. Conclusions: Patients with chronic conditions and health professionals believe that green exercise improves physical activity engagement, and it would be beneficial if incorporated in the rehabilitation process. There are challenges to overcome to make therapeutic green exercise for people with chronic conditions more accessible.